The relationship between depression and risk of violence in portuguese community-dwelling older people - Mendes, FM (2022)
Background: Mental disorders are highly prevalent in older people, being depression a predominant disorder. Evidence points to a possible relationship between depression and violence against older people. Nonetheless, the role of the depressive symptomology severity in the risk of violence against older people remains unclear. Thus, this study’s main objective was to analyze the relationship between geriatric depressive symptomatology and the risk of violence against older people. Methods: This exploratory study involved 502 community-dwelling older persons aged 65 to 96 years (73.3 ± 6.5). Measures were performed using the Geriatric Depression Scale and the Risk Assessment of Violence against the Non- Institutionalized Elderly scale. Results: One hundred nineteen older people (23.7%) had mild/moderate depressive symptomology, and twenty-six (5.2%) had severe depressive symptomology. There were significant relationships between the severity of depressive symptomatology and the risk of violence (p < 0.05). The presence of depressive symptomatology increased the likelihood of being victims of violence, particularly among women (odds ratio: 2–8, p < 0.05). Conclusions: The severity of depressive symptomatology plays an essential role in the risk of violence against community-dwelling older people. Moreover, it was found that older persons with depression symptomatology were at higher risk of being victims of violence. Our study findings support the need for protective measures within mental health national or regional policies to prevent depression and violence against community-dwelling older people.